Al-Muqaranah Baina ath-Thariqah al-Mubasyarah bi Wasilah Bithaqah al-Istdzkar wa ath-Thariqah as-Sam’iyyah asy-Syafawiyyah bi Tiqniyyah Qul wa Unzhur li tarqiyah Maharah al-Kalam - Idam Kholid Nasution (STAIN Bengkalis, 2021)
This study was aimed to find out the comparison between student’s speaking skill and to find out some of the factors that influenced it. Based on that the researcher want to compare between using Direct Method with Flash Card Media and Audio Lingual Method with Look Say Exercise Technique in improving student’s speaking skill by practice. In this study, the researcher used comparative research by using the comparison of two classes. The subject of this study were the tenth grade students of MAN 2 pekanbaru and the object of this study were Direct Method with Flash Card Media and Audio Lingual with Look and Say Exercise technique and speking skill, the population of study were 379 students of MAN 2 pekanbaru , the sample of this study were 67 students, the instrument to collect the data used (1) Test and (2) documentation, the analysis was used SPSS V.16.